Guiding through the Fog: Financial statement complexity and voluntary disclosure - Guay, Wayne; Samuels, Delphine; Taylor, Daniel (Journal of Accounting and Economics, 2016)
A growing literature documents that complex financial statements negatively affect the information environment. In this paper, we examine whether managers use voluntary disclosure to mitigate these negative effects. Employing cross-sectional and within-firm designs, we find a robust positive relation between financial statement complexity and voluntary disclosure. This relation is stronger when liquidity decreases around the filing of the financial statements, is stronger when firms have more outside monitors, and is weaker when firms have poor performance and greater earnings management. We also examine the relation between financial statement complexity and voluntary disclosure using two quasi-natural experiments. Employing a generalized difference-in-differences design, we find firms affected by the adoption of complex accounting standards (e.g., SFAS 133 and SFAS 157) increase their voluntary disclosure to a greater extent than unaffected firms. Collectively, these findings suggest managers use voluntary disclosure to mitigate the negative effects of complex financial statements on the information environment.